Media Language and Logic as Essential Knowledge in Modern Media - Makharadze, Ia (European Scientific Journal, ESJ, 2024)
The language of the media, his word, is obviously not a logo. So what he said about the logical nature of language might seem like an exaggeration here, but the point is that words, in a sense, never lose the ’magic’ of impact that writing, and especially poetry, clearly convinces us of. With regard to the media’s treatment of the logos of speech, it is of particular significance here that the most striking circumstance emphasized by researchers is that in the distant past, through logos, people’s minds were imbued with an idea of the power of speech, a peculiar kind of verbal influence. And this, of course, has to affect the way people interact on a day-to-day basis, which is primarily through language. Therefore, all verbal, intellectual communication, including the communication act through the mass media, should be highly instructed by teachers about the logical nature of words and ancient dialogical thinking. Moreover, the logos of divine wisdom (pre-Christian or Christian) of Plato and Socrates’ dialogic thought is related to the elevation of human nature, the deepening of human wisdom. The concept of the logos and the ancient Greek dialogues profoundly imply the influence on the human consciousness and, therefore, its corresponding behavior, but all this must be subordinated to the will of God by the demands of the logos order.